The Effect of Financial Stress on Psychological Distress with Social Support as a Moderator in Karawang Manufacturing Employees - Tita Atiatul Maula; Lania Muharsih; Mohammad Iqbal (Ilomata International Journal of Social Science, 2026)
The manufacturing sector is a major contributor to Indonesia’s economic growth; however, its demanding work environment increases the risk of psychological distress among employees. Karawang Regency, as one of Indonesia’s key industrial areas, employs a large manufacturing workforce. Financial stress resulting from economic instability is considered an important factor influencing employees’ psychological well-being. This study aims to examine the effect of financial stress on psychological distress and investigate whether social support moderates this relationship among manufacturing employees in Karawang. Using a quantitative approach, primary data were collected through a Google Forms survey involving 312 employees of a manufacturing company in Karawang. The study employed the Kessler Psychological Distress Scale (K10), Financial Stress Scale (FSS), and Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using Moderated Regression Analysis (MRA) with JASP software. The results indicate that financial stress has a significant positive effect on psychological distress, while social support has a significant negative effect. Furthermore, the interaction effect demonstrates that social support significantly weakens the impact of financial stress on psychological distress. The model explains 51.7% of the variance in psychological distress. These findings suggest that financial stress is a significant risk factor for employee mental well-being, whereas social support functions as an important protective factor. Therefore, organizations should strengthen social support mechanisms in the workplace to help reduce the adverse psychological effects of financial stress and improve employee well-being.